Pengaruh Kepercayaan, Karakteristik Konsumen Dan Motivasi Terhadap Keputusan Pembelian Honda Scoopy Di Kota Bima - Roy Romansyah; Amirulmukminin (Journal of Student Research, 2023)
This study aims to determine and analyze the effect of trust, consumer characteristics and motivation on purchasing decisions for Honda Scoopy in Bima City. This type of associative research with primary data in and sourced from the research instrument in the form of a Likert-scale questionnaire so that the type of data used is quantitative data. The research population is all consumers who have bought a Honda Scoopy in the city of Bima, the exact number of which is not known. The sample of this research was 96 respondents using purposive sampling technique. data collected by observation, questionnaires and literature study. Data analysis techniques using validity test, reliability test, classic assumption test multiple regression, multiple correlation coefficient, t test and f test. The results showed that trust, consumer characteristics and motivation had a significant effect on purchasing decisions for Honda Scoopy in Bima City.